2010
DOI: 10.4049/jimmunol.1000246
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans Cells Serve as Immunoregulatory Cells by Activating NKT Cells

Abstract: Ultraviolet exposure alters the morphology and function of epidermal Langerhans cells (LCs), which play a role in UV-induced immune suppression. It is generally believed that UV exposure triggers the migration of immature LCs from the skin to the draining lymph nodes (LNs), where they induce tolerance. However, because most of the previous studies employed in vitro UV-irradiated LCs, the data generated may not adequately reflect what is happening in vivo. In this study, we isolated migrating LCs from the LNs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 49 publications
2
61
0
5
Order By: Relevance
“…The UVR-induced effect on contact hypersensitivity responses measured only after 84 d was not significant. This is similar to a recent report (36), although these mice were sensitized at the UV-irradiated site (local UVR-induced immunosuppression). All studies confirm the longlasting effects of UVR.…”
Section: Discussionsupporting
confidence: 79%
“…The UVR-induced effect on contact hypersensitivity responses measured only after 84 d was not significant. This is similar to a recent report (36), although these mice were sensitized at the UV-irradiated site (local UVR-induced immunosuppression). All studies confirm the longlasting effects of UVR.…”
Section: Discussionsupporting
confidence: 79%
“…In Bacci et al's experiment with mice irradiated with UVB, it occurred only after 24 hours [21]. However, in Fukunaga et al's study, after UVB irradiation of mice with a dose of 1000-2000 J/m 2 , the number of LCs in the epidermis returned to baseline after 63 days [22].…”
Section: Effects Of Uv Radiation On the Number Of Lcs In The Epidermismentioning
confidence: 84%
“…This phenomenon may be partly explained by the decreased expression of alpha4 integrin by LCs and its impaired binding to fibronectin as well as the reduction in surface chemokine receptor CCR7. In the study involving mice in vivo, Fukunaga et al [22] showed that exposure to UVB (270-290 nm) triggered the migra-tion of mature LC to the skin draining lymph nodes. The authors also observed prolonged LCs survival in the lymph nodes, i.e.…”
Section: Effects Of Uv On Immunological Functions Of Lcs: Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Langerhans hücreleri lenf bezlerinde NKT hücreleriyle birliktedir ve yakınında yer alırlar. UV ışımasını takiben lenf bezlerine göç eden CD1d+ Langerhans hücreleri orada, IL-4 sekresyonu yapmaları için NKT hücrelerini uyarırlar 32 . UV ışıması yapılmış farelerden alınan haptenle konjuge Langerhans hücreleri NKT hücreleri olmayan hayvanlara (CD1-/-ya da Jα18-/-fareler) injekte edildiğinde immunsupresyon oluşturulabilir 2 .…”
Section: Cis-urocanicasit(cis-uca)veuvışımasıunclassified